The (near) Future of Central Bank Digital Currencies : Risks and Opportunities for the Global Economy and Society. - Bilotta, Nicola. (Global Politics and Security Series, 2021)
This book provides an overview of the approaches, features and implications of CBDCs. It briefly explores the current literature on CBDCs and provides concrete example of this innovation's stage of development.